THE ROLE OF ORGANIZATIONAL CULTURE AND PROFESSIONALISM IN IMPROVING LECTURER PERFORMANCE WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR BASED ON SPIRITUAL (OCBBOS) AS INTERVENING VARIABLES - Setyowati, Trias; Tyas, Wenny Murtalining; Qomariah, Nurul (Universitas Brawijaya, Indonesia, 2023)
The role of lecturers is very important in improving the performance of tertiary institutions. The performance of tertiary institutions can be seen from the university accreditation scores in certain periods. This study aims to analyze and determine the direct and indirect effects of organizational culture (X1) and professionalism (X2) on performance through organizational citizenship behavior based on spirituality (Z) as an intervening variable at Muhammadiyah University in East Java. The population in this study were all lecturers teaching at Muhammadiyah University in East Java (UM Surabaya, UM Gresik, UM Ponorogo, UM Jember, UM Sidoarjo), totaling 1,242 people. This study determined a sample of 200 lecturers using the proportional simple random sampling method. Data analysis used descriptive statistical analysis and Structural Equation Modeling (SEM) -AMOS and the Sobel test. The results showed that organizational culture had no significant positive effect on lecturer performance. Lecturer professionalism has a significant positive impact on performance. Organizational culture has a significant positive effect on spiritual-based OCB. Lecturer professionalism has a positive effect on spiritual-based OCB. Spiritual-based OCB has a significant positive effect on performance. Organizational culture has a significant effect on performance through spiritual-based OCB. Lecturer professionalism has a significant effect through spiritual-based OCB on performance.